Resocialization Of Convicts in The Czech Republic: The Role of The Prison System in Promoting Reintegration into Society - Vlach, František; Stárek, Lukáš (Jurnal Cita Hukum, 2025)
The article focuses on the execution of imprisonment in the Czech Republic and its objectives and responsibilities in promoting the reintegration of convicted persons into society. The prison system's primary mission is to ensure the safety of society and protection from offenders, as well as to provide systematic social support and penitentiary care. Specially trained staff help convicts understand their behaviour and the reasons for breaking the law and acquire new moral standards, skills, and knowledge. This approach emphasises the transformation of convicts to reduce the risk of reoffending and facilitate their return to society as active, independent and contributing members. The practical and social-adaptive skills developed during their sentence are crucial for successful re-socialisation and minimising re-offending risks. The study offers insight into the principles and practices of the Czech penitentiary system, emphasising its rehabilitative and preventive functions. The current Russo-Ukrainian war has caused an influx of Ukrainian refugees, including those who may have committed crimes in the Czech Republic. This situation places increased demands on the prison system, which must respond not only to the general needs of convicts, but also to the specific challenges arising from their cultural, legal and social context.